2011
DOI: 10.1073/pnas.1010875108
|View full text |Cite
|
Sign up to set email alerts
|

Host and viral ecology determine bat rabies seasonality and maintenance

Abstract: Rabies is an acute viral infection that is typically fatal. Most rabies modeling has focused on disease dynamics and control within terrestrial mammals (e.g., raccoons and foxes). As such, rabies in bats has been largely neglected until recently. Because bats have been implicated as natural reservoirs for several emerging zoonotic viruses, including SARS-like corona viruses, henipaviruses, and lyssaviruses, understanding how pathogens are maintained within a population becomes vital. Unfortunately, little is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
192
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(208 citation statements)
references
References 35 publications
12
192
0
4
Order By: Relevance
“…Infection prevalence of other viruses, including coronaviruses and rabies, shows seasonal dynamics in bats [25][26][27]. The increase in susceptible hosts and contact rates during and following the birthing period may drive infection dynamics [28], though overwinter hibernation has also been shown to be important in temperate bat systems for rabies [29]. Amman et al [24] identified MARV in Rousettus aegyptiacus bats in a cave in Uganda by using polymerase chain reaction (PCR) and viral isolation, and discovered that the disease occurred in pulses in older juvenile bats (approx.…”
Section: Introductionmentioning
confidence: 99%
“…Infection prevalence of other viruses, including coronaviruses and rabies, shows seasonal dynamics in bats [25][26][27]. The increase in susceptible hosts and contact rates during and following the birthing period may drive infection dynamics [28], though overwinter hibernation has also been shown to be important in temperate bat systems for rabies [29]. Amman et al [24] identified MARV in Rousettus aegyptiacus bats in a cave in Uganda by using polymerase chain reaction (PCR) and viral isolation, and discovered that the disease occurred in pulses in older juvenile bats (approx.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding viral persistence in bat populations is challenging because seemingly ideal ecological traits for explosive pathogen transmission such as high mobility and colonial aggregation contrast with the limited supply of new susceptible individuals generated by characteristically long-lived and slow-reproducing host species. Consequently, epizootiological models of bat viruses have required complex immunological or behavioral mechanisms to achieve long-term persistence, such as waning maternal immunity or an extended incubation period through hibernation (4)(5)(6). These studies also demonstrated the power of a combined field, experimental, and modeling approach for identifying persistence mechanisms in bats, but such holistic investigations are still absent for most systems (3).…”
mentioning
confidence: 99%
“…14,16 Some studies suggest that if climatic conditions change, individuals are likely to relocate to new areas and roosts. 18,19 Due to its ecological plasticity, the vampire bat can easily adapt to new landscapes modified by humans where loss of native plant cover, increased forage and greater abundance of domestic livestock have created suitable conditions for their breeding and feeding. 4,8 In Mexico, it is expected that the combination of changes in land use and changes in global and regional climates will produce species distributional shifts, including reservoirs and vectors for infectious diseases, modifying the patterns of infectious Climate change on bovine paralytic rabies in Mexico DOI: http://dx.doi.org/10.21753/vmoa.…”
Section: Introductionmentioning
confidence: 99%